2016
DOI: 10.1016/j.jcp.2016.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Lax–Wendroff procedure for numerical boundary conditions of convection–diffusion equations

Abstract: We consider numerical boundary conditions for high order finite difference schemes for solving convection-diffusion equations on arbitrary geometry. The two main difficulties for numerical boundary conditions in such situations are: (1) the wide stencil of the high order finite difference operator requires special treatment for a few ghost points near the boundary; (2) the physical boundary may not coincide with grid points in a Cartesian mesh and may intersect with the mesh in an arbitrary fashion. For purely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…We refer to Goldberg andTadmor (1978, 1981) for earlier discussions on this procedure. This procedure has been generalized to moving boundaries in Tan and Shu (2011), and to convection-diffusion equations in Lu et al (2016). A simplified version, for which the (more expensive) ILW procedure is only applied to several lower-order derivatives and standard extrapolation is applied to the remaining ones, has been introduced in Tan, Wang, Shu and Ning (2012) and analysed for stability in Zhang (2016, 2017).…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…We refer to Goldberg andTadmor (1978, 1981) for earlier discussions on this procedure. This procedure has been generalized to moving boundaries in Tan and Shu (2011), and to convection-diffusion equations in Lu et al (2016). A simplified version, for which the (more expensive) ILW procedure is only applied to several lower-order derivatives and standard extrapolation is applied to the remaining ones, has been introduced in Tan, Wang, Shu and Ning (2012) and analysed for stability in Zhang (2016, 2017).…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…So far, the ILW method has been mostly used on hyperbolic equations including conservation laws [216,217,218,146] and Boltzmann type models [71], which involve only first order spatial derivatives in the equations. Very recently, Lu et al extended this methodology to convection-diffusion equations [157]. It turns out that this extension is highly non-trivial, as totally different boundary treatments are needed for the diffusion-dominated and the convection-dominated regimes.…”
Section: Inverse Lax-wendroff Type Boundary Conditions For Finite Difmentioning
confidence: 99%
“…It turns out that this extension is highly non-trivial, as totally different boundary treatments are needed for the diffusion-dominated and the convection-dominated regimes. A careful combination of these two boundary treatments has been designed in [157], in order to obtain a stable and accurate boundary condition for high order finite difference schemes when applied to convection-diffusion equations, regardless of whether they are convection or diffusion dominant.…”
Section: Inverse Lax-wendroff Type Boundary Conditions For Finite Difmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is of course delicate, especially with finite-difference discretizations on non-conforming meshes. In this context, a very successful technique is the inverse Lax-Wendroff approach, which was introduced in [40], rendered more computationally efficient in [41], and further studied and extended for example in [24,27,28]; a quite up-to-date review may be found in [39]. A modified procedure enhancing its accuracy and stability has been proposed in [43].…”
Section: Introductionmentioning
confidence: 99%